High viscosity of ionic liquids causes rate retardation of Diels-Alder reactions - Kumar, Anil; Pawar, Sanjay S. (Science China-Chemistry, 2012)
Second order rate constants, k (2) have been determined for three bi-molecular Diels-Alder reactions to demonstrate that the high viscosity of ionic liquids can be a detrimental property in carrying out Diels-Alder reactions, if ionic liquids are employed as solvent media. It is possible to enhance the reaction rates of the reaction if a co-solvent is mixed in pure ionic liquid used as a solvent.
Keywords: Diels-Alder reactions; ionic liquids; kinetics; viscosity